Retrospective comparison of cyclophosphamide and mycophenolate mofetil in lupus nephritis at Groote Schuur Hospital nephrology unit - Sogayise, Phelisa (Department of Medicine, 2021)
Background. Lupus nephritis (LN) can be complicated with requirement for kidney replacement therapy and death. Efficacy of induction therapies using mycophenolate mofetil (MMF) or intravenous cyclophosphamide (IVCYC) has been reported from studies, but there is limited data in Africans comparing both treatments in patients with proliferative LN. Methods. This was a retrospective study of patients with biopsy-proven proliferative LN diagnosed and treated with either MMF or IVCYC in a single centre in Cape Town, South Africa, over a 5-year period. *e primary outcome was attaining complete remission after completion of induction therapy. Results. Of the 84 patients included, mean age was 29.6 ± 10.4 years and there was a female preponderance (88.1%). At baseline, there were significant differences in estimated glomerular filtration rate (eGFR) and presence of glomerular crescents between both groups (p ≤ 0.05). After completion of induction therapy, there was no significant difference in remission status (76.0% versus 87.5%; p = 0.33) or relapse status (8.1% versus 10.3%; p = 0.22) for the IVCYC and MMF groups, respectively. Mortality rate for the IVCYC group was 5.5 per 10,000 person-days of follow-up compared to 1.5 per 10,000 person-days of follow-up for the MMF group (p = 0.11), and there was no significant difference in infection-related adverse events between both groups. Estimated GFR at baseline was the only predictor of death (OR: 1.0 [0.9–1.0]; p = 0.001). Conclusion. This study shows similar outcomes following induction treatment with MMF or IVCYC in patients with biopsy-proven proliferative LN in South Africa. However, a prospective and randomized study is needed to adequately assess these outcomes.